THE MERCURY USE DURING THE AMAZON GOLD RUSH - Bonotto, Daniel Marcos [UNESP] (2009)
UNESP Univ Estadual Paulista Julio Mesquita Filho, IGCE Inst Geociencias & Ciencias Exatas, Dept Petrol & Metalogenia, BR-13506900 Rio Claro, SP, Brazil